PWE-294 Microparticle dependent procoagulant activity and thrombin generation is increased in patients with cirrhosis induced coagulopathy. (28th May 2012) - Jairath, V; Harrison, P; Stanworth, S; Collier, J; Murphy, M; Barnes, E
Abstract : Introduction: Recent data suggests stable cirrhotics may have a hypercoagulable phenotype. Microparticles (MPs) are submicron plasma particles formed by the exocytic budding of cell membranes and play an important role in haemostasis due to phosphatidylserine (PS) surface expression which provides a phospholipid surface for assembly of coagulation enzymes and/or the expression of tissue factor (TF), the primary initiator of coagulation. To determine whether MPs may contribute to this hypercoagulable phenotype, we assessed microparticle associated functional procoagulant and phenotypic characteristics in cirrhotics. Methods: 72 consecutive cirrhotics and 30 healthy volunteers were recruited. Platelet free plasma (PFP) was prepared by two centrifugations and MP-free plasma (MP-FP) by filtration of PFP through a 200 nm microparticle filtration unit. Microparticle (MP) associated procoagulant activity (PCA) was measured using the STA Procoag PPL (phospholipid) assay (Stago Diagnostics) and MP associated thrombin generation (TG) measured using the calibrated automated thrombogram (CAT). For the CAT assay TG was initiated by adding CaCl2 and 1 pM tissue factor, but no phospholipid (PRP reagent), therefore TG was dependent upon phospholipid present in the sample. Flow cytometry (LSRII) was used to determine MP size, number and cellular origin using marker specific antibodies. Results: PFP from cirrhotics generated significantly more thrombin than healthy volunteers reflected in the ETP (1374.3 vs 1142.6 nM/min, p=0.04), the peak (101.0 vs 66.5 nM, p=0.001) and a shorter time to peak (13.0 vs 14.2 min, p=0.03). Similarly, MP associated PCA was significantly increased in cirrhotics (65.9±13.2 s), compared to healthy volunteers (74.6±13.9 s, p=0.005). Following filtration of MPs >200 nM in size, there was a large reduction in ETP and peak in both cirrhotics and healthy volunteers, with prolongation of both the time to peak and PPL time. There was significant inverse correlation between the PPL assay and parameters of the TG test [ETP (r=−0.57, p<0.001), Peak (r=−0.43, p<0.001)]. Cirrhotic patients had high levels of Annexin V binding PS positive MPs compared to controls (1412 vs 279 per u/l, p<0.05). Conclusion: Microparticle dependent procoagulant activity and thrombin generating capacity is increased in plasma from cirrhotics. High levels of annexin-V positive procoagulant MPs are a likely key and previously undescribed mechanism contributing to the hypercoaguable phenotype observed in cirrhotics. Competing interests: None declared.